Investor Perceptions of the Quality of Sharia Financial Reporting and Its Impact on Investment Decisions Study on Companies Listed in the Jakarta Islamic Index (JII) - Sembiring, Maria Dinda Sabrina (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to analyze investor perceptions of the quality of Islamic financial reporting and its impact on investment decisions in the Jakarta Islamic Index (JII). The background of this research is based on the growth of Indonesia's Islamic capital market capitalization, but has not been followed by a significant increase in retail investor participation. This research uses the Descriptive Method with a qualitative approach to collect and analyze literature related to the research topic. The research shows that the quality of Islamic financial reporting significantly influences investors' perceptions. The more positive investors' perceptions of the quality of Islamic financial reporting, the more likely they are to invest in stocks in the Jakarta Islamic Index. However, regulators and issuers need to improve disclosure standards and socialization. This study has real-world consequences, such as the suggestion that OJK and the National Sharia Council (DSN) create more detailed reporting guidelines and that investors should be educated about Islamic financial standards.